Can bureaucracy be beautiful? - Frederickson, H. George (2000)
Public administration has long been understood to be both a science and an art. In its artful aspects, public administration can also, in fact, be beautiful. At their very best, public organizations and processes have forms, designs, experiences, and languages which are beautiful and compelling. It is this beauty and its potential which draws us to public work. And, there is very great beauty in ideas of high and noble purpose and in the organizations and processes we build to achieve those ideas. - Reproduced
Keywords: Bureaucracy - United States; Bureaucracy